Islamic Values in Syahadat Cinta Novel by Taufiqurrahman Al-Azizy - Hariyani Hariyani (Jurnal Pendidikan Humaniora, 2014)
Nilai Keislaman dalam Novel Syahadat Cinta Karya Taufiqurrahman Al-AzizyAbstract: This study aimed to examine the Islamic values contained in the Syahadat Cinta novel by Taufiqurrahman Al-Azizy. The focus of this study were (1) the value of faith; (2) the value obedient worship; and (3) the value of good moral. Metode used in this research is interpretitif. The results of the study include three things. First, research the value of faith, are (1) the value of faith in God; (2) Faith in angels; (3) Faith in the Book of Allah; (4) Faith in the prophets and apostles; (5) Faith in the end; (6) Faith in the qada and qadar. Secondly, the research value of obedient worship are: (1) obey thaharah worship; (2) obey praying; (3) obey zakat; (4) obey the fasting; (5) devout hajj. Third, research on the value of good moral are (1) character to God; (2) character to yourself; (3) character to the family; (4) character to the neighbors and the community; and (5) character to the environment. The value of much revealed is the value of faith in God because this novel tells the story of the faith of a someone who emigrated from the wrong path toward the right path.Key Words: islamic values, novel Abstrak: Penelitian ini bertujuan untuk meneliti nilai keislaman yang terdapat dalam novel Syahadat Cinta karya Taufiqurrahman Al-Azizy. Fokus penelitian ini adalah (1) nilai keimanan; (2) nilai ketaatibadahan; dan (3) nilai keakhlakmuliaan. Metode yang digunakan dalam penelitian  ini adalah penelitian interpretitif. Hasil penelitian mencakup tiga hal. Pertama, penelitian nilai keimanan yaitu (1) nilai iman kepada Allah; (2) iman kepada malaikat; (3) iman kepada kitab Allah; (4) iman kepada nabi dan rasul;  (5) iman kepada hari akhir; (6) iman kepada qada dan qadar.  Kedua, penelitian nilai ketaatibadahan  yaitu (1) taat ibadah thaharah; (2) taat ibadah shalat; (3) taat ibadah zakat; (4) taat ibadah puasa; (5) taat ibadah haji . Ketiga, penelitian terhadap nilai keakhlakmuliaan yaitu (1) akhlak kepada Allah; (2) akhlak kepada diri sendiri; (3) akhlak kepada keluarga; (4) akhlak kepada tetangga dan masyarakat; dan (5) akhlak kepada lingkungan. Nilai yang banyak diungkap adalah nilai keimanan kepada Allah karena novel ini mengisahkan jalan keimanan seorang tokoh yang berhijrah dari jalan yang salah menuju jalan yang benar. Kata kunci: nilai keislaman, novel